Where Do We Go From Here? Charleston Conference Proceedings 2015 2016
DOI: 10.5703/1288284316308
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Bananas: Collection Assessment of Patron‐Driven Acquisitions

Abstract: insights-library-archivaland-information-sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Experimentations with DDA models revealed that a comprehensive assessment of such programs should use of a variety of metrics in order to gain a more granular understanding of program performance and the level of satisfaction of all stakeholders [10,11]. Many DDA assessment studies have since concluded that the model fulfills librarian expectations and user needs [12], has a better cost per use than other traditional ebooks packages [13,14], is advantageous for specific disciplines [13], and provides collection development benefits for academic libraries overall [15,16]. Some studies assert, nevertheless, that there is still yet insufficient data to demonstrate conclusively the benefits of DDA over traditional collection development practices [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentations with DDA models revealed that a comprehensive assessment of such programs should use of a variety of metrics in order to gain a more granular understanding of program performance and the level of satisfaction of all stakeholders [10,11]. Many DDA assessment studies have since concluded that the model fulfills librarian expectations and user needs [12], has a better cost per use than other traditional ebooks packages [13,14], is advantageous for specific disciplines [13], and provides collection development benefits for academic libraries overall [15,16]. Some studies assert, nevertheless, that there is still yet insufficient data to demonstrate conclusively the benefits of DDA over traditional collection development practices [17,18].…”
Section: Introductionmentioning
confidence: 99%